Atividade residual de 2,4-D sobre a emergência de soja em solos com texturas distintas - Silva, Ferdinando Marcos Lima [UNESP]; Cavalieri, Sidnei Douglas; José, Alcebíades Rebouças São; Ulloa, Santiago Miguel; Velini, Edivaldo Domingues [UNESP] (Revista Brasileira de Herbicidas, 2011)
This research aimed to evaluate the 2.4-D residual activity over soybean emergence in soils with distinct textures. The experiments, each one with a distinct soil type (clay sand and clay), were conducted in greenhouse conditions, in a randomized entirely design, in factorial scheme 6x2+1 with treatments constituted by the combination of six application period: 0, 3, 5, 7, 10 and 14 days before soybean sown (DBS) and two 2.4-D (502.5 e 1,005 g e.a. ha-1) doses, besides an absolute check without herbicide application. 2.4-D residual activity was evaluated through the emergence speed index (ESI), germination percentage (%), visual phytointoxication (%), plant high (cm) and soybean plants dry biomass (g) at 26 DBS. In both soil types, 2.4-D residual activity was observed, ranging in function of herbicide dose and time period between herbicide application and soybean sown. The effect was more pronounced in plants grown on cland soil where there was higher phytointoxication and reduction of dry biomass in relation to the check, mainly at the treatment where herbicide was sprayed and soybean genotype V-Max sowed in following.

Objetivou-se com este trabalho avaliar a atividade residual do herbicida 2,4-D sobre a emergência de soja em solos de texturas distintas. Os experimentos, um com cada classe de solo (textura média e argilosa), foram conduzidos em casa de vegetação, em delineamento inteiramente casualizado, no esquema fatorial 6x2+1, sendo os tratamentos constituídos pela combinação de seis épocas de aplicação: 0, 3, 5, 7, 10 e 14 dias antes da semeadura (DAS) da soja e duas dosagens de 2,4-D (502,5 e 1.005 g e.a. ha-1), mais uma testemunha absoluta sem aplicação do herbicida. A atividade residual do 2,4-D foi avaliada por meio do índice de velocidade de emergência (IVE), porcentagem de emergência (%), fitointoxicação visual (%), altura (cm) e biomassa seca (g) das plantas de soja aos 26 dias após a semeadura. Em ambos os solos, a atividade residual do 2,4-D foi observada, com variação em função da dosagem e do período de tempo entre a aplicação e a semeadura da soja. O efeito foi mais pronunciado nas plantas cultivadas em solo de textura média, onde houve maior fitointoxicação e redução da biomassa seca em relação à testemunha, principalmente, no tratamento onde o herbicida foi aplicado e a soja, cultivar V-Max, semeada em seguida.
2,4-D residual activity over soybean emergence in soils with distinct textures
Keywords: Herbicide; Persistence; Phytointoxication; Herbicida; Persistência; Fitointoxicação